KEMAMPUAN BACA TULIS ANAK DISLEKSIA DENGAN KONDISI KECERDASAN INTELEKTUAL BORDERLINE - Ro'fah Syahidah, - (2022)
The phenomenon of dyslexia contains many risks related to child growth and development and has an impact on the developmental barriers of generations. The purpose of this study is to describe the ability to read and write, the factors that cause dyslexia, and types of dyslexia in children who have borderline intellectual intelligence. The relevant theories to achieve this goal are the theory of signs of dyslexia by Hargio (2012), the causes of dyslexia developed by Christo, Davis, and Brock (2009), and the theory of classification of dyslexia by Sidiarto (2007). The method used in this research is descriptive qualitative method with observation, interview, and documentation techniques. This study resulted in (1) literacy, (2) factors causing dyslexia, and (3) types of dyslexia in children who have borderline intellectual intelligence. The conclusion of this study is that Naira as a research subject has poor reading skills. Five phenomena occur 1) Addition of unnecessary affixes; 2) Addition of unnecessary phonemes; 3) Incorrect pronunciation of phonemes; 4) Wrong word pronunciation; and 5) Addition of words. In addition, his writing ability has six forms. Six forms of written language, including 1) the omission of vowels; 2) The omission of consonants; 3) Wrong morpheme writing; 4) Wrong word writing: 5) Substitution of letters; and 6) Wrong repeating words. Then found the factors causing the subject to experience dyslexia, namely phonological and morphological deficits. Lastly, Naira is dyslexic with language impairment and visual-auditory disconnection.